IMPLEMENTATION OF EDUCATION MANAGEMENT INFORMATION SYSTEM IN THE LEARNING PROCESS AT SMKN 1 CIJULANG - Irpan Ilmi; Neneng Nurmalasari; Eji Wijaya (Bajang Institute, 2021)
This research describes the Implementation of Education Management Information System (SIMDIK) in the learning process at SMKN 1 Cijulang. Educational management information systems are developed to meet the needs of institutions / schools, where schools want in the learning process to use information systems in an effort to answer the challenges of the 21st century that require institutions / schools to develop management information systems (SIM) to create learning that is not monotonous and saturated for students in the classroom. This study uses qualitative methods using observation, interviews and documentation as data collection techniques. The results of this study show that the Implementation of Education Management Information System (SIMDIK) at SMKN 1 Cijulang in the learning process utilizing learning application systems namely Edmodo, E-Raport and Smart Board for Axioo classes in creating interactive learning is good enough. Supporting factors in the implementation of educational management information system in SMKN 1 Cijulang is the existence of a dapodic information system that is useful to register students, educators and education personnel (PTK), the support and cooperation from various parties in infrastructure or human resources in supporting SMKN 1 Cijulang as a school that implements digitalization system. The obstacles encountered in the learning process at SMKN 1 Cijulang include elderly teachers who have difficulty in using management information system (SIM) applications.